Rare alleles within the CYP2E1 (MEOS system) could be associated with better short-term health outcome after acute methanol poisoning - Hubacek, Jaroslav A; Pelclova, Daniela; Seidl, Zdenek; Vaneckova, Manuela; Klempir, Jiri; Ruzicka, Evzen; Ridzon, Petr; Urban, Pavel; Fenclova, Zdenka; Petrik, Vit; Diblik, Pavel; Kuthan, Pavel; et al. (Basic & clinical pharmacology & toxicology, 2015)
Genetic polymorphisms influence the metabolism of ethanol and methanol, but the potential effects of genetic predisposition on the clinical course, outcome and short-term health sequelae of acute methanol poisoning are unknown. To evaluate the role of the MEOS system in methanol poisoning, we analysed the effect of three polymorphisms (RsaI - rs2031920; PstI - rs3813867; insertion/deletion I/D) within the CYP2E1 enzyme (MEOS system) in 50 adult survivors of methanol poisoning and compared their genotype frequencies with 460 controls. The minor allele frequencies of all three polymorphisms were below 5% in both groups. We did not detect significant differences in the genotype frequencies between survivors of methanol poisoning and controls (p = 0.34 for the RsaI variant; p = 0.59 for the PstI variant and p = 0.21 for the I/D polymorphism). The carriers of at least one minor allele in the CYP2E1 gene had less severe clinical symptoms and better short-term outcome after acute poisoning. Variants within the CYP2E1 gene are likely not significant genetic determinants of acute methanol poisoning (if survivors are analysed), but they may influence the severity of methanol poisoning and its visual/central nervous system (CNS) outcome.
Keywords: alely; methanol; Humans; lidé středního věku; přežívající; polymorfismus genetický; Female; Aged; mladý dospělý; dospělí; frekvence genu; Alleles; Survivors; senioři; lidé; Genotype; Cytochrome P-450 CYP2E1; Polymorphism, Genetic; Adult; ženské pohlaví; stupeň závažnosti nemoci; cytochrom P-450 CYP2E1; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Methanol; Gene Frequency; Severity of Illness Index; Young Adult; genotyp; mužské pohlaví